Metaverse dalam Pembuatan dan Penggunaannya: Kegiatan Metaverse di Bidang Bisnis Online dan Pengaturannya di Indonesia - Muhammad Abbydzar Nur Fauzan; Enni Soerjati Priowirjanto (Publikasi Indonesia, 2023)
Metaverse is a platform in a three-dimensional virtual world, where users can explore the 3-dimensional world with other Internet users using avatars by interacting like in the real world. Users can also have the same opportunity to change their economic situation in the virtual world. The metaverse becomes a means to do many things, such as social activities by creating communities in the metaverse, meetings, teaching and learning activities, and economic activities. The researcher will discuss about analyzing the impact of the metaverse on the development of the digital economy in Indonesia and what regulations are appropriate for the activities in the metaverse world. The research method used in this research is the Normative Juridical Method and Qualitative Method in which researchers will quote secondary data such as laws and regulations, scientific journals, and law books.